(untitled) - Novalis, Susann (San Francisco, CA, 2001)
Designed specifically for Access power users, not experienced programmers, this task-oriented guide will help readers build on their Access experience and develop the VBA programming skills needed to create custom database applications.
Keywords: Database management,Hệ quản trị cơ sở dữ liệu